Quality assessment of family planning counseling in health and treatment centers, affiliated to Tehran University of Medical Sciences - Pakgohar; M. (M.Sc); Rahimikian; F. (M.Sc); Mehran; A. (M.Sc); Mohammadi; T. (M.Sc) (Tehran University of Medical Sciences, 2002)
The present study is a descriptive one made for the purpose of quality assessment of family planning counseling in health and treatment centers affiliated to Tehran University of Medical Sciences in year 2000. 410 client of the Family Planning Social Services who had attended 25 health and treatment centers affiliated to Tehran University of Medical Sciences were participated in this research study. A checklist was completed through the observation of family planning counseling sessions. The finding and results of this study showed that personnel's behaviour and the quality of family planning counseling for the majority of samples in the first section have been suitable. In the section of the history taking from clients helping them to select suitable method and to determine next appointment, data for the majority of samples in this study have been in an average level. In the section of need understanding of clients introductory methods providing information the audiovisual training equipments used during family planning counseling, explanation of way of utilizing the selected method, and finally the environment for family planning counseling have not been suitable for majority of the samples. The findings of this study can be beneficial for public health planning in order to improve the quality of the family planning services.